Impact of Lanthanum Doping on the Structural, Electrical, and Magnetic Properties of BaFe12O19 Nano Particles - Gilani , Zaheer Abbas; Ul Islam, Siraj; Khan Asghar, H. M. Noor ul Huda; Hussain, Rafaqat; Ahmad Shaikh, Furhaj (Journal of Materials and Physical Sciences, 2021)
These ferrites had been considered very highly valuable electronic materials for many decades. The ferrite compounds have a hexagonal structure. Nano structural and dielectric features for BaFe12-xLaxO19 (0.00, 0.25.0.50, 0.75, 1.00) nano Hexaferrite (NHFs) was studied present research. The Ba NHF prepared via sol-gel technique. The single phase of barium Nano Hexaferrites of various sample was confirmed by XRD, the average crystalline size calculated in the range of 5 to 13 nm.The lattice parameter lattice constant, X-ray density, bulk density, micro strain and lattice strain are the parameters of XRD which are also calculated. The different parameters of XRD also show the decreasing and increasing trend which is totally depend on the concentration. The hexagonal structure also confirmed by FTIR. There are two frequency band are investigated which are ?1 and ?2 which are associated with tetrahedral stretching band and octahedral stretching band respectively. The different frequency band are calculated at different frequency like ?1=500 to 540 and also ?2 = 413. The dielectric properties also measured in the frequency range from 1 MHz to 3 GHz. There are many others parameters are calculated in dielectric properties such as real and imaginary electric modulus, real and imaginary impedance, dielectric constant, dielectric loss and tangent loss. The parameters of dielectric also showing decreasing and increasing in trend. The real and imaginary impedance plot changes as when the frequency increases, the all the specimens converge on one another, and at a higher frequency, the impedance exhibits coherent nature, which is due to the discharge of space charges.